The Bessermian Holiday Akayashka and Terminology Associated with its Celebration - Sergey A. Maksimov (Publishing house "Sreda", 2022)
The paper is devoted to the traditional Bessermian holiday akayashka associated with the beginning of spring agricultural work. The ritual complex of the holiday lasted for three or four days, and each day had its own name: arafa, akayashka ~ akashka, akayashka kelyan. Relevance. The Udmurt ritual cycle akashka (beserm. akayashka) is described in sufficient detail by researchers of the 19th - early 21st centuries. There have been attempts in recent works to reconstruct the origin and evolution of ritual elements. However, some of the earlier descriptions in similar studies have been left without due attention. The etymologies of some terms related to the celebration of akayashka are not fully disclosed, or they are questionable and need further research or clarification. Conclusion. In this paper, for the first time, the etymologies of the words cholpan (a mallet used to beat on wood to exorcise evil spirits on the first day of the celebration of akayashka) and argar (a rite on the eve of Akayashka with a request from the Almighty God for a harvest) are revealed; the reason for the creation of the name of the rite burdo shөd 'winged soup', the analogues of which are absent in Udmurt dialects, is defined; the reasons for the difference in the celebration of the rites of the akayashka ~ akashka ~ gershyd cycle, which have the same source of origin, are also specified.